AN OPHTHALMIC HEALTH SURVEY IN NORTHERN IRAN - Kh. Moradpour; M. Motabar (Tehran University of Medical Sciences, 1974)
The province of Rudsar is located in the Caspian littoral zone of Iran. In 1970 an ophthalmic health survey was carried out in 25 units, which were selected by random sampling in these areas. A total of 2,165 persons were examined and the results of this evaluation have been prepared in 6 parts, consisting of ophthalmic conditions and health customs, infectious eye diseases, visual status and diseases, blindness and its causes, eye complications of malnutrition, and other eye disease. The prevalence of trachoma is 24% and of conjunctivitis 11.2%, but infectious eye diseases are mild in these areas and their complications are very rare, and trachoma is deviated mainly to inclusion conjunctivitis. Visual defect are important problem in the Rudsar area; 17.8% of the persons examined of 10 years of age and over, had visual defects. The most important causes of visual defects are refraction abnormalities, especially myopic astigmatism and contact. Visual defects are more prevalent in females than in males. Of the total number of persons examined, 2.63% had infectious eye diseases, 2.77% had blindness in at least one eye and 56.7% of the blindness was caused by cataracts. The eye complications of avitaminosis A and ariboflavinosis were observed, especially in rural areas. The establishment of an ophthalmic clinic, the use of a mobile dispensary unit for diagnosis, procedures for introducing patients to the ophthalmic clinic, and special procedures for the health of school children would be beneficial and are recommended for the control of ophthalmic disease. It is also necessary to have a special survey on toxoplasmosis, an investigation for clarification of the causes of differences in visual defects in males and females, and a survey on the causes of blepharitis.